IMPLEMENTATION OF MANAGEMENT FUNCTIONS IN THE WASTE MANAGEMENT SYSTEM OF AGRO-INDUSTRIAL PRODUCTION - Dubnevych, Yurii; Binert, Olesya; Lyzak, Mykhailo (Public Management and Policy, 2025)
Agro-industrial production is an important component of the economy but is accompanied by significant waste generation, creating environmental and economic challenges. Inefficient waste management leads to waste accumulation, environmental pollution, and the loss of potential raw materials for secondary use. The implementation of management functions in the waste management system of agro-industrial production enables the creation of effective mechanisms for control, coordination, and optimization of disposal processes. The study demonstrated that effective waste management in agro-industrial production is possible through the implementation of management functions, specifically: Planning – developing strategies to reduce waste and increase the level of recycling; Organization – optimizing logistical processes for waste collection and transportation; Motivation – applying economic incentives and environmental regulations; Control – establishing a monitoring system for waste management efficiency. A waste management model has been proposed, incorporating modern technologies and environmental management mechanisms, which contribute to reducing the environmental burden and increasing resource efficiency. The results confirm the necessity of implementing a systematic approach to agro-industrial waste management. The application of management functions enhances organizational processes, reduces waste volumes, and improves the economic performance of enterprises. The introduction of advanced waste recycling technologies promotes resource conservation and the development of a circular economy. The implementation of management functions in the waste management system of agro-industrial production is a crucial step toward ensuring the sustainable development of the agricultural sector. Optimizing waste management processes reduces the negative impact on the environment, increases enterprises’ ecological responsibility, and fosters economic growth. The proposed approaches can be used to develop national and regional strategies for waste management in agro-industrial production.